Suicidal ideation and suicide attempts among older recipients of public welfare assistance in Japan. Issue 10 (20th July 2022) - Kino, Shiho; Stickley, Andrew; Nishioka, Daisuke; Ueno, Keiko; Saito, Masashige; Ojima, Toshiyuki; Kondo, Naoki
Abstract : Background: The high suicide rate among older adults is an important public health issue. Financial insecurity has been linked to suicidal behaviour. Despite this, as yet, there has been little research on suicide-related behaviours among older recipients of public welfare. This study will examine if suicidal ideation and suicide attempts are more prevalent in older recipients of public welfare assistance in Japan. Methods: This cross-sectional study analysed data from 16 135 adults aged ≥65 years who participated in the 2019 wave of the Japan Gerontological Evaluation Study. Information was obtained on receiving public welfare assistance, lifetime suicidal ideation and attempts, and a variety of covariates. Poisson regression analysis with robust variance estimates was used to examine associations. Results: Suicidal ideation was reported by 4.8% of the participants, while the corresponding figure for attempted suicide was 2.2%. In fully adjusted analyses public welfare recipients had an almost 1.5 times higher prevalence of lifetime suicidal ideation (prevalence ratio, PR 1.47, 95% CI 1.02 to 2.13), and an almost two times higher prevalence of attempted suicide (PR 1.91, 95% CI 1.20 to 3.04) when compared with their counterparts not receiving public welfare assistance. Conclusion: Older recipients of public welfare have a higher prevalence of suicidal behaviour in Japan. An urgent focus is now warranted on this vulnerable population to determine the specific factors underlying this association.